2012
DOI: 10.7860/jcdr/2012/4443.2568
|View full text |Cite
|
Sign up to set email alerts
|

The Abuse of Multiple Gastrointestinal Antibiotics: A Case Report

Abstract: The abuse of non dependence producing substances has been rarely reported. However, this can be a significant social problem and it may complicate psychiatric disorders like the anxiety states. We are reporting here, a case of the prolonged abuse of multiple gastrointestinal antibiotics like metronidazole, mebendazole and albendazole. The patient had fortunately not developed any overt toxicity from the overuse of these drugs. He was diagnosed with the generalized anxiety disorder with the anankastic personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The population-based observational analyses found the positive associations of long-term antibiotic use during early life with anxiety and depression, which were consistent with previous published epidemiological study [14] and animal study [15]. In particular, growing experimental evidences suggested that longterm antibiotic use during early life may have significant detrimental consequences for increasing vulnerability to mental disorders [14,16,18,34,35]. The antibiotic treatment would alter the gut microbiome [36], which may influence gut-brain communication and then alter the trajectory of brain development [15].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The population-based observational analyses found the positive associations of long-term antibiotic use during early life with anxiety and depression, which were consistent with previous published epidemiological study [14] and animal study [15]. In particular, growing experimental evidences suggested that longterm antibiotic use during early life may have significant detrimental consequences for increasing vulnerability to mental disorders [14,16,18,34,35]. The antibiotic treatment would alter the gut microbiome [36], which may influence gut-brain communication and then alter the trajectory of brain development [15].…”
Section: Discussionsupporting
confidence: 88%
“…For instance, Lurie et al [14] observed that long-term antibiotic exposure increased the risk of depression and anxiety in a nested case-control study. In another case, it was reported that a patient was diagnosed with the generalized anxiety disorder after abuse of multiple gastrointestinal antibiotics [16]. And an adolescent patient developed symptoms of delirium during treatment with cephalexin [17].…”
Section: Introductionmentioning
confidence: 99%